Effectiveness of Lavender Aromatherapy on Anxiety in SMK Prima Indonesia Girls During PMS - Mukaromah, Nahdiyatul (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Around 30–80% of women of reproductive age experience physical and psychological Premenstual Syndrome (PMS) symptoms, including anxiety, for which lavender aromatherapy is a recommended complementary treatment. The purpose of this study is to determine the effect of aromatherapy on the anxiety levels of female students during PMS. Methods this research employed a quantitative method with a quasi-experimental approach using a Pretest-Posttest design without a control group. The study was conducted at SMK from August 1 to October 25, 2022. The population consisted of all female students in grade X who had experienced menarche, totaling 85 students aged 13-17 years old. Data collection was done using the Hamilton Anxiety Rating Scale (HARS) questionnaire, comprising 14 standard questions. Univariate and bivariate analyses were conducted using the T-Test. The results revealed a p-value of 0.000, which is less than α (0.05), indicating that lavender aromatherapy had a significant effect on reducing anxiety levels in female students during PMS. Before the treatment, most respondents experienced moderate anxiety, but after the aromatherapy, more respondents shifted to experiencing mild anxiety. Lavender aromatherapy is significantly effective in reducing anxiety levels in female students during premenstrual syndrome (PMS).